Efficacy of Acacia arabica gum as an adjunct to scaling and root planing in the treatment of chronic periodontitis: A randomized controlled clinical trial - Rameshwari Singhal; Vivek Agarwal; Pavitra Rastogi; Richa Khanna; Shuchi Tripathi (Elsevier, 2018)
Aim: The aim of the present study was to explore the adjunctive use of Acacia arabica gel in the treatment of chronic periodontitis. Methods: Single centre, randomised, triple blind, controlled trial on mild to moderate chronic periodontitis patients; Group I (SRP + Acacia arabica, n = 40) and Group II (SRP + placebo, n = 40); were analysed for clinical improvements in periodontal pocket depth (PPD) and clinical attachment levels (CAL) at baseline, 15 and 90 days on application of gels. Gingival index and plaque index were assessed as secondary parameters. Results: Statistically significant PPD reduction (p < .05) and CAL gain (p < .05) was observed with use of Acacia arabica gel. The reduction in sites with moderate PPD was observed more among Group I than Group II and the difference was statistically significant (p = .001). Secondary outcome variables; Plaque Index and Gingival Index showed better resolution with Acacia arabica gel. Conclusion: Acacia arabica leads to better clinical outcomes in patients with mild to moderate chronic periodontitis with effective antiplaque and anti-gingivitis action. It may be recommended adjunct to SRP for maintenance in patients with mild to moderate chronic periodontitis. Keywords: Acacia gum, Anti plaque, Anti gingivitis, Periodontitis, Periodontal pocket, Scaling and root planing, Treatment